A new species of Brasixenos Kogan & Oliveira, 1966 (Strepsiptera: Xenidae) from Mexico - Quintos-Andrade, Gerardo; Valenzuela-González, Jorge Ernesto; Palmeros-Sánchez, Beatriz; Torres-Moreno, Raymundo (Zootaxa, 2023)
The first record of the genus Brasixenos Kogan & Oliveira is presented for Mexico with the description of B. mesoamericanus, a species found in localities from central Veracruz state. The males of this species are characterized by the mouthparts shape, wing venation, and genitalia. The females are identified by their reduced size and the mandible morphology. Polybia plebeja is identified as the host of this species. The biology and distribution of Brasixenos, and challenges in the study of this genus in the Neotropical region are discussed.